Evaporative electrical energy generation via diffusion-driven ion-electron-coupled transport in semiconducting nanoporous channel. (February 2021) - Yoon, Sun Geun; Jin, Huding; Lee, Won Hyung; Han, Junghyup; Cho, Yong Hyun; Kim, Youn Sang
Abstract: Water is one of the plentiful and ubiquitous resources on earth. Due to this characteristic, much efforts have been made to utilize various fluidic phenomena, such as fluidic transport and energy conversions. Recently, in conjunction with an advent of diverse nanomaterials, studies of these fluidic phenomena have been expanded to nanometric domains in those materials, possessing a high surface-to-volume ratio and unique solid-liquid interfacial effects. However, as an understanding of the nanofluidic effects therein was deficient, detailed studies of ionic transports and corresponding ion-solid interfacial interactions are still required. Herein, an evaporation-driven fluidic energy production in molybdenum disulfide (MoS2 ) and silica nanoparticle (SiO2 NP)-based nanoporous channel was demonstrated by a translation of an evaporation-driven electro-diffusion of ions in the nanofluidic domain into a charge carrier effect in the semiconducting MoS2 layer via interfacial coulombic field drag effect. The revealing results showed that the semiconducting nanofluidic channels can be utilized to induce an ion-charge carrier-coupled effect beyond conventional electro-kinetic effects in insulating conduits. Our finding could provide understandings of water-nanomaterials interfacial interactions for developing advanced nanofluidic energy conversion systems. Graphical Abstract: ga1 Highlights: Highly stable and continuous electricity generation in an evaporation-driven energy conversion device was demonstrated with a semiconducting molybdenum disulfide/silica nanoparticle composite. Continuous ion-electron interactions at an electrolyte-nanoconduit interface, a key factor for a continuity of evaporation-driven electricity generation, were verified firstly through analyses of ion specificity and concentration dependency in the device. A mechanism was verified with a coulombic ion-electron-coupled transport in the nanocapillarity-semiconducting electrode interface. Applications of energy harvesting and electrochemical process were proposed through the device.